Pengaruh Layanan Bimbingan Kelompok Terhadap Perkembangan Sosial - Mentari, Sinta Nurul; Sugiharto, Dwi Yuwono Puji (Universitas Negeri Semarang, 2016)
This research based existing phenomena in class V SD N 4 Kutamendala Tonjong Brebes that shows low level of social development. The purpose of the research was to get information or empirical finding about influence group guidance service the social development, through to the fifth grade student’s class of SD N 4 Kutamendala Tonjong Brebes. The population was all student of the V class in SD N 4 Kutamendala Tonjong Brebes, which consenst of 28 students. Purposive sampling technique was used in this study, samples were 10 students. Data collection techniques using social development scale. The instrument has been tested for validity using Pearson product moment and reliability of the instrument with alpha formula. Data analysis used descriptive percentage, and wilcoxon. The result of study showed there was increment of social development thrught group guidance service with Tcount = 0 < Ttable = 8. The conclusion of study was group guidance service could be influence social development. It is hoped that the teacher as a guide can be more intensively do group guidance service to the students as an alternative strategy to help students increase social development.